Single Leg Balance Training: A Systematic Review. Issue 2 (April 2022) - Marcori, Alexandre J; Monteiro, Pedro H M; Oliveira, Júlia A; Doumas, Michail; Teixeira, Luis A
Single leg balance training promotes significant increments in balance control, but previous reviews on balance control have not analyzed this form of balance training. Accordingly, we aimed to review the single leg balance training literature to better understand the effects of applying this training to healthy individuals. We searched five databases—PubMed, EMBASE, Scopus, Lilacs, and Scielo—with the following inclusion criteria: (a) peer-reviewed articles published in English; (b) analysis of adult participants who had no musculoskeletal injuries or diseases that might impair balance control; and (c) use of methods containing at least a pre-test, exclusive single leg balance training, and a post-test assessment. We included 13 articles meeting these criteria and found that single leg balance training protocols were effective in inducing balance control gains in either single- or multiple-session training and with or without progression of difficulty. Balance control gains were achieved with different amounts of training, ranging from a single short session of 10 minutes to multiple sessions totaling as much as 390 min of unipedal balance time. Generalization of balance gains to untrained tasks and cross-education between legs from single leg balance training were consistent across studies. We concluded that single leg balance training can be used in various contexts to improve balance performance in healthy individuals. These results extend knowledge of expected outcomes from this form of training and aid single leg balance exercise prescription regarding volume, frequency, and potential progressions.